MENGELOLA PERUBAHAN ORGANISASI DI ERA AI, ADAPTASI BUDAYA DAN PERILAKU - putri, anggelina; khairunisa, Hanum; Tahang, Heriyanti (Al-Mumtaz: Jurnal Manajemen Pendidikan Islam, 2026)
In the era of Artificial Intelligence (AI), organizations are facing increasing demands to undergo rapid and comprehensive transformation. This transformation encompasses not only technological aspects but also workplace culture and employee behavior to ensure that changes are implemented effectively. Visionary leadership, an open mindset toward innovation, and an adaptive and collaborative organizational culture are essential in this process. This study aims to explore how organizations manage changes resulting from the implementation of AI, with a particular focus on the adaptation of workplace culture and employee behavior. The study employs a literature review approach by examining various academic journals and scholarly sources to understand change management strategies, shifts in organizational values, and forms of employee adjustment to new technologies. The findings of the literature review indicate that AI integration encourages organizations to shift from conventional structures toward more flexible and responsive models. Transformational leadership plays a crucial role in fostering an innovative environment, enhancing employee trust, and reducing resistance to change. The main challenges faced include digital skills gaps, concerns regarding data privacy, and fears of human roles being displaced by machines. Organizations that successfully manage change generally invest in reskilling and upskilling programs, strengthening soft skills, and implementing AI-based e-HRM systems to improve the efficiency of recruitment and training processes. In the context of education and the public sector, AI also contributes to administrative efficiency, personalized learning, and data-driven decision-making. However, ethical issues, data protection, and algorithmic transparency remain significant concerns. In conclusion, the success of digital transformation in the AI era largely depends on an organization’s internal readiness to synergize technology, culture, and human resources. A human-centric approach serves as an essential foundation for maintaining a balance between technological innovation and organizational sustainability in the future.